Fragmentasi Kewenangan dalam Pengelolaan Data Pemilih dan Dampaknya terhadap Pencatutan Identitas pada Pemilu 2024 - Kurniawan, Basuki; Nugroho, Jati; Purwanti, Henny; Firmansyah, Hendika Candra Nicolas (Universitas Islam Indonesia, 2026)
The phenomenon of citizens' personal data misappropriation into political party membership through the SIPOL application in the 2024 Election reveals a regulatory disharmony within Indonesia's digital democracy ecosystem. The digitalization of political party verification, originally intended to enhance administrative efficiency, has in practice triggered privacy rights violations due to the unauthorized use of National Identification Numbers (NIK). This study focuses on two main issues: firstly, the implications of regulatory inconsistencies between the Personal Data Protection Act (PDP Act) and the General Elections Commission Regulation (PKPU) for the effectiveness of restoring the rights of victims of identity theft within the electoral information system; secondly, the necessary restructuring of electoral personal data protection to achieve substantive electoral justice. To address these issues, this study aims to analyse the effectiveness of legal protection for victims of data misuse, evaluate the KPU’s operational performance in handling public complaints, and examine the implications of regulatory fragmentation for legal certainty and substantive justice. The research method employed is socio-legal research with a single case study model in Jember Regency using purposive sampling techniques. Data were collected through in-depth interviews with KPU commissioners and victims of data misappropriation, and analyzed using statutory and conceptual approaches. The results of this study indicate that the currently available protection mechanisms remain administrative-procedural and have not been able to provide complete rights restoration. This is evidenced by the existence of